Ethnicity/Race and Age-Specific Variations of Serum AMH in Women—A Review - Kotlyar, Alexander M.; Seifer, David B. (Frontiers in Endocrinology, 2021)
Purpose of Review In this review, we summarize ethnic/race- and age-related variation in AMH and discuss the underpinnings behind these differences. Recent findings Anti-mullerian hormone (AMH) has become a widely used method of ovarian reserve testing over the last 15 years. Numerous studies have shown substantial ethnic/race and age-related differences. When compared to age-matched Caucasian women, AMH levels tend to be lower in black and Hispanic women. Chinese women tend to have significantly greater AMH levels prior to age 25 than Caucasian women. When considering subpopulations within ethnicities, at least one study noted lower AMH levels among Maya women compared to other Hispanic women. Age exhibits a positive trend with AMH up until at least 25 years of age with a consistent decline after 34 years of age extending to menopause. Summary AMH levels are highly variable among ethnicities and race with higher age-matched levels typically seen in Caucasian women. Age does not exhibit a consistent linear relationship with AMH, but a consistent decline is seen starting in the third decade of life and proceeding to menopause.